Computer-assisted Minimally Invasive Transforaminal Lumbar Interbody Fusion May Be Better Than Open Surgery for Treating Degenerative Lumbar Disease. Issue 6 (July 2017) - Tian, Wei; Xu, Yun-Feng; Liu, Bo; Liu, Ya-Jun; He, Da; Yuan, Qiang; Lang, Zhao; Han, Xiao-Guang
Abstract : Study Design: This study was a retrospective review of prospectively collected clinical data. Objective: To evaluate the clinical and radiologic outcomes of computer-assisted minimally invasive spine surgery transforaminal lumbar interbody fusion (CAMISS-TLIF) and open TLIF for the treatment of 1-level degenerative lumbar disease. Summary of Background Data: Minimally invasive TLIF is becoming increasingly popular; however, the limited space and high rate of hardware complications associated with this method are challenging to surgeons. Computer-assisted navigation has the potential to dynamically show the fine anatomic structures, which could theoretically facilitate minimally invasive spine procedures. Methods: Sixty-one patients underwent 1-level TLIF procedures (30, CAMISS-TLIF; 31, open TLIF). The computer-assisted navigation system was used for CAMISS-TLIF, whereas conventional fluoroscopy was used for open TLIF. Demographic, operative, visual analog scale, and Oswestry disability index data were collected. Screw insertion was assessed by computed tomography, and radiologic fusion based on Bridwell grading was evaluated 2 years after surgery by independent investigators. Results: The CAMISS-TLIF group had significantly less blood loss, postoperative drain, need for transfusion, and initial postoperative back pain; earlier rehabilitation; and shorter postoperative hospitalization than the open TLIF group, whereas CAMISS-TLIF took longer surgical time than open TLIF. However, no significant differences between the 2 groups in visual analog scale scores and Oswestry disability index were observed at 3 months, 1 year, and 2 years postoperatively. A total of 93.33% and 73.39% of screws in the CAMISS and open groups, respectively, had no pedicle perforation ( P =0.016), and the fusion rate was similar in both groups ( P =0.787). Conclusions: Computer-assisted navigation facilitated minimally invasive spine surgery-TLIF. CAMISS-TLIF was superior to open TLIF for treating 1-level degenerative lumbar disease, although it required longer operation time in the initial stage. CAMISS-TLIF showed several benefits compared with open TLIF, including less intraoperative blood loss, postoperative drainage, and pain; earlier rehabilitation; and shorter postoperative hospitalization.